PELAKSANAAN PEMBELAJARAN TATAP MUKA TERBATAS : STRATEGI PEMBELAJARAN DI SMP SWASTA PASCA PANDEMI COVID 19 - Iwan Ramadhan; Muhammad Agus Hardiansyah; Haris Firmansyah; Maria Ulfah; Husni Syahrudin; Suriyanisa Suriyanisa (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
The purpose of this research is to find out the strategy of the limited face-to-face learning process that is applied at Mujahidin Private Junior High School. The method used in this research is a descriptive qualitative research method. As in qualitative research that researchers obtain data through direct observation and refine it with interviews and obtain data in the form of documentation. The results of this study are the strategy of implementing limited face-to-face learning processes in accordance with learning guidelines during the pandemic, such as facilities and infrastructure for implementing health protocols that require teacher guidance. Not only that, the application of learning strategies to technology-based learning media and school readiness and teachers as homeroom teachers who play a role in managing learning that is more than one subject at the middle education level. Thus the strategy of implementing learning at the basic education level has more tasks that must be managed by the teacher and of course, it is in accordance with the situation and conditions in the pandemic so that learning strategies that have limitations in time can achieve the goals of middle-level education to shape the character of students.